Phenotypical and genotypical expansion of autosomal-dominant KDM1A-related neurodevelopmental disorder spectrum: a case report - Burkart, Sebastian; Spanjaard, Melanie; Kaufmann, Lilian; Hinderhofer, Katrin; Schaaf, Christian P.; Ries, Markus; Hempel, Maja (American journal of medical genetics, 2025)
KDM1A-related neurodevelopmental disorder (CPRF, OMIM #616728) is characterized by cleft palate, global developmental delay, and distinct facial gestalt, but phenotypic knowledge of this ultra-rare autosomal dominant disorder is limited. Here, we report on a 13-year-old boy with a novel heterozygous, likely pathogenic germline missense variant in exon 16 of KDM1A with developmental delay, hypotonia, mild intellectual disability, and unspecific facial features but without palate abnormalities. Notably, this first reported individual without palate abnormalities highlights the variable expressivity of this feature in the KDM1A-related phenotype. Furthermore, this case report expands knowledge on the phenotypic spectrum, including intellectual disability with global developmental delay, muscular hypotonia, and variable dysmorphic anomalies, highlighting the value of individual case studies in clinical research.